Legal Position of The Senate in Constantinople - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
It is very well known that the Senate in Constantinople was founded in 324, during the reign of the Emperor Constantine the Great. However, during his rule the Senate was not on the level of the imperial institution. Constantine’s son and successor Constantius II decided to equalize legally the Senates of Rome and Constantinople. Although since 324 till 476 there were two Senates (in Rome and in Constantinople), it seems that legally we had just one institution with the two seats.